Analysis of lymphoma subtypes, involved sites, and treatment outcomes in primary gastrointestinal B-cell lymphomas: A subset analysis within the PELÉ study of brazilian centers. - Duffles, Guilherme; Silveira, Talita; Clé, Diego; Perruso, Luiza; Carneiro, Guilherme; Baptista, Renata; Gaiolla, Rafael Dezen [UNESP]; Perensin, Fernanda; Borducchi, Davimar; Galvão, Fábio; Silva, Bárbara; Campos, Ana Luiza; et al. (American Society of Hematology, 2025)
Abstract Introduction: Primary gastrointestinal tract lymphomas (PGITL) are rare but are the most common site of extranodal presentation. The main subtypes include diffuse large B-cell lymphoma (DLBCL) and marginal zone lymphomas (MZL). PGITL are intrinsically associated with certain risk factors such as Helicobacter pylori (HP) infection, immunodeficiency, and idiopathic inflammatory bowel disease. There is a lack of comprehensive data on the epidemiology and clinical features of PGITL in South America. Therefore, this study aims to evaluate the clinical and epidemiological aspects of PGITL from Brazilian centers. This analysis is part of the Primary Extranodal Lymphoma Effort (PELÉ) study. Methods: This retrospective, multicenter observational study was conducted across Brazilian centers from 2009 to 2024, reviewing cases of B-cell non-Hodgkin lymphomas presenting primarily as extranodal gastrointestinal disease. Cases were categorized into upper digestive tract (buccal mucosa, pharynx, esophagus), stomach, and lower digestive tract (small and large intestine, rectum, anus). Clinical stages were classified as: (I) isolated organ involvement; (II) organ involvement with minimal contiguous lymph node involvement; (III) multiple organ involvement. Staging was performed using PET/CT or CT of the neck, chest, and abdomen, complemented by endoscopy and colonoscopy. Data were collected and managed via the REDCap platform (Vanderbilt). Statistical analysis was performed using IBM SPSS v.24. Survival estimates were calculated with the Kaplan-Meier method, and curves were compared with the Log-Rank test. Cox regression models identified prognostic factors for overall survival (OS), event-free survival (EFS), and disease-free survival (DFS), with a significance level set at 5%. Results: A total of 206 patients were included. The median age at diagnosis was 63 years (range 27–90), with most patients being white (68.4%) and male (55.8%). The stomach was the most common site of involvement (149 patients, 72.3%), followed by the lower digestive tract (35 patients, 17%) and upper digestive tract (22 patients, 10.7%). The main lymphoma subtypes were DLBCL (n=114, 55.3%), MZL (n=84, 40.8%), and others (n=8, 3.9%). Among DLBCL patients, 69 (60%) had gastric disease, with 95 (85%) presenting at CS I/II, and 53% were classified as low-risk by IPI. In the MZL subgroup, 77 (91.6%) had gastric disease, 74 (89%) were CS I/II, and 79% were low-risk by IPI. In the DLBCL subgroup, 104 patients (91.2%) received rituximab-based chemotherapy (RC), achieving a complete remission (CR) rate of 73%. In the MZL subgroup, radiotherapy (RT) was administered to 35 patients (41.6%), with 25 (29.8%) receiving RT as the sole treatment. Antibiotics for HP infection were prescribed to 25 patients (29.8%). Using the GELA score for response assessment, complete histological remission (CHR) was observed in 76% of 55 gastric MZL cases. Among patients treated with RT as sole therapy, CHR was achieved in 82% (19/23), while those treated solely with antibiotics had a CHR of 68% (17/25). With a median follow-up of 39 months (range 3–197) for DLBCL and 39.5 months (range 4–149) for MZL, the estimated 5-year EFS and OS were 76% (95% CI: 68–84%) and 87% (95% CI: 81–93%) for DLBCL, and 81% (95% CI: 71–91%) and 94% (95% CI: 86–100%) for MZL, respectively. The median survival time was not reached for DLBCL and was 115 months (73–157) for MZL. The 5-year DFS for DLBCL and MZL, both involving only the stomach, was 94% vs. 83% (p=0.02). Multivariate analysis identified ECOG performance status 2–4 as a risk factor for OS and EFS in the DLBCL cohort. Conclusions: This analysis of PGITL revealed a predominance of gastric involvement, primarily as localized disease with low-risk IPI scores. DLBCL and MZL accounted for the majority of cases. RT was the primary treatment modality for MZL, used as either sole or combined therapy. It also achieved higher rates of CHR compared to antibiotics for HP infection. Patients with gastric DLBCL had a better 5-year DFS compared to those with gastric MZL, but the median survival time was not reached for the DLBCL group. This study has limitations, including its retrospective nature and the absence of centralized pathology and imaging review. Nevertheless, it provides important insights into the clinical aspects and treatment outcomes of PGITL in Brazilian centers. Data collection will continue within the framework of the PELÉ study.